Para-adventure: a hyper-dynamic problem for the inclusive coach. Issue 7 (3rd July 2019) - Collins, Loel; Simon, Scott; Carson, Howie J.
Abstract: Recent research has recognized sports coaching as complex, chaotic and cognitively taxing for coaches. Against this backdrop, the present paper explores challenges faced by high-level coaches working with disabled performers. Specifically, it seeks to understand how coaches create mental models of performance in adventure sports and para-canoe. Five coaches were purposively sampled and underwent a semi-structured interview. A thematic analysis revealed conceptualizing the mental model as being mechanically related for all and as including a social construction within the para-canoe coaches. Reflection on the coaching process and on personal characteristics were perceived as important to individualized inclusive coaching. Coach training should particularly emphasize the need for critical judgement and decision-making skills within a similarly oriented social structure of coaches and support staff where applicable.